2014
DOI: 10.12980/apjtb.4.2014c744
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices related to cutaneous leishmaniasis in an endemic focus of cutaneous leishmaniasis, Southern Iran

Abstract: In this study, insufficient knowledge of community about infection nature, vector, transmission mode and preventive measures of CL, highlights the needs for a health education initiative to enhance the awareness of people about CL. This would improve inhabitants' contribution in control program of CL in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 12 publications
6
39
0
1
Order By: Relevance
“…Educated people are more aware of transmission of protozoan infection and they may apply the necessary measurements to avoid the infection. Increase of health awareness among the community is crucial and is an important requirement for prevention and control of parasitic diseases including intestinal protozoan in this and any other similar areas of the country [26]. A case control study in south of Tehran revealed that knowledge and practices of children significantly reduced the rate of infection in group covered by health education program [27].…”
Section: Discussionmentioning
confidence: 99%
“…Educated people are more aware of transmission of protozoan infection and they may apply the necessary measurements to avoid the infection. Increase of health awareness among the community is crucial and is an important requirement for prevention and control of parasitic diseases including intestinal protozoan in this and any other similar areas of the country [26]. A case control study in south of Tehran revealed that knowledge and practices of children significantly reduced the rate of infection in group covered by health education program [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore this strategic approach in the fight against leishmaniasis should be considered in public health and educational programs for people. Media can raise the level of awareness of people on control of leishmaniasis too (Sarkari et al 2014). In perspective, transmission modeling needs to be undertaken in such infectious disease systems to appreciate and elucidate better the dynamics of involved parameters (Parvizi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For successful implementation of health education programs, the target population should have an adequate understanding of each program. 30 Respondents from Qianshan Prefecture were less knowledgeable than those from Nanqiao District, which may be because of the health education programs implemented in Nanqiao District after SFTS cases and cluster infections occurred. On the other hand, a previous study has reported gender as a predictive factor of positive KAP scores.…”
Section: Discussionmentioning
confidence: 94%